Ivatan-Filipino-English dictionary the cultural dictionary of Batanes - Hidalgo, Cesar A. (Academics Foundation, 1998)
A cultural dictionary containing Ivatan-Filipino-English words and their meanings intended for the Ivatans and for those who wish to understand the Ivatan language and culture who are Filipino and English speakers. It also provides Ivatan expressions, proverbs, idioms and metaphors.